Second language pragmatics from theory to research - Culpeper, Jonathan 1966-; Mackey, Alison 1966-; Taguchi, Naoko 1967- (Routledge, Taylor & Francis Group, 2018)
Second Language Pragmatics: From Theory to Research aims to reinvigorate this field, pointing the way forward to new methodologies that can drive, or be driven by, new theoretical developments. With a unique combination of leading international expertise in general pragmatics, L2 pragmatics, and research methodology, the authors describe in detail the methods, including the most recent techniques, by which pragmatics of all types can be pursued in L2 contexts. This volume argues that L2 pragmatics research needs to expand from its initial base by drawing from a wider range of sources, such as corpus linguistics and psycholinguistics. Clear, accessible and practical, Second Language Pragmatics will be valuable to novice and seasoned researchers alike in second language pragmatics, general pragmatics, and second language acquisition courses--back cover
Keywords: Pragmatics / Research; Second language acquisition / Research; Interlanguage (Language learning) / Research; Intercultural communication / Research; Language and languages / Study and teaching / Research; Fremdsprachenlernen; Pragmatik